MODIFIKASI TAPIOKA DENGAN KOMBINASI PROSES HIDROLISA ASAM LAKTAT DAN OKSIDASI HIDROGEN PEROKSIDA UNTUK MENINGKATKAN DAYA KEMBANG - Desti Permata Sari; Devi Marietta Siregar; Siswo Sumardiono (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
Indonesia is one of the largest wheat importer. Wheat is consumed by most of Indonesian. Nowadays, the government is trying to find alternative material to substitute wheat with local material named cassava. Cassava is chosen because it has good potential to be developed in Indonesia. Native starch requires long time in reacting and cooking. Hence, the native starch with high purity can be readily modified by physical, chemical and enzyme process to many diversified products to improve the starch functionality and, consequently, encourage more industrial application. On this research, cassava starch modification is produced by combination lactic acid hydrolysis and oxidation using hydrogen peroxide. The results of this research are expected to be a food innovation in small and medium industries.The conclusion that we get is combination lactic acid hydrolysis and oxidation using hydrogen peroxide can increase the expansion of starch. The highest values for the sum of carbonyl dan carboxyl occured at pH 5, hydrogen peroxide concentration 2 %, temperature 40oC, and baking expansion 3,03 cm3/gr. The condition of oxidation that presented the carbonyl and carboxyl content of starch similar to the sun-dried cassava starch. The oxidation with H2O2 provides after hydrolisis cassava starch and produces more homogenous product. Optimal composition of the use of tapioca starch modification bread is 25% of modified tapioca and 75% of wheat flour which has baking expansion 3,03 cm3/gr.